MOBILITAS SOSIAL PETANI SAWAH DI DESA PENYASAWAN KECAMATAN KAMPAR KABUPATEN KAMPAR (STUDI KASUS : ALIH FUNGSI LAHAN PERTANIAN) - Putri Yuliani; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to find out and analyze the process pf rice farmer mobility and the factors that cause mobility in Penyasawan Village Kampar District Kampar Regency. This research is a descriptive qualitative research with observation, interview and documentation techniques. This study uses the technique of determining this study determined by Purposive Sampling techniques, then Purposive Sampling is taking samples with certain considerations or deliberate sampling and aiming. The theory used is the Theory of Social change. This research subject used as a source of information contained in the study was carried out as many as 6 people. The results of this study found that the process of social mobility of lowland rice farmers differed in each informant. There were several informants in the transfer process who had to ask for their extended family’s permission, even though the land they owned was inherited from each of their parents, they still had to ask permission from the large family to move the land. But there were also informants who were given this research not asking permision from their extended family. The process of social mobilitiy of rice paddy farmers in Penyasawan Village is very influential in their work, where they have to work hard tu support their families and the transfer of lang affects the education of their children. But the land of each informant that the researcher found was that the land had moved from paddy farmer farms to non-farm rice farmers such as rubber plantations, oil palm plantations, house and business buildings for swallow and in factors that affected the social mobility of rice farmers in Penyasawan Village there were several factors found in this study, namely: economic factors, age factors, generation factors and natural factors. Keywords: Famer, Social Mobility, Land Conversion